Diamond particle reinforced aluminum alloy flux-cored wire and laser welding method thereof

Through the combination of diamond particles-enhanced aluminum alloy flux core wire and laser welding technology, defect problems such as oxidation, pores, and cracks in aluminum alloy welding are solved, and the high strength, wear resistance and high thermal conductivity of the welds are achieved, and the service life of the welds is extended.

CN119839498AActive Publication Date: 2025-04-18STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510164727.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-18
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

During aluminum alloy welding, defects such as oxidation, pores, cracks and other defects are prone to occur, which affects the quality and service life of the weld, especially in the welding of complex structural parts and special-shaped aluminum alloy plates.

Method used

Diamond particle-reinforced aluminum alloy flux-core wire is prepared by ball mill mixing and rolling, combined with laser welding technology, using the high thermal conductivity of diamond and the reaction of Si with diamond to generate SiC enhanced interface combination, stabilize the melt pool and reduce pores and cracks.

Benefits of technology

It significantly improves the strength, wear resistance and thermal conductivity of the weld, reduces the risk of thermal stress and deformation during welding, extends the service life of the welded parts, and improves the welding efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839498A_ABST
    Figure CN119839498A_ABST
Patent Text Reader

Abstract

The invention discloses a diamond particle reinforced aluminum alloy flux-cored wire which is prepared by using commercial common 6061 series aluminum alloy powder as a base material, adding metal powder capable of forming carbides, using diamond as a reinforced phase, adding graphite powder as a lubricant, mixing the raw materials, and preparing the diamond particle reinforced aluminum alloy flux-cored wire. A 6061 aluminum alloy or pure aluminum hollow pipe is used as a flux-cored wire sheath, and the diamond particle reinforced aluminum alloy flux-cored wire is obtained through rolling annealing. The invention further discloses a laser welding method of the diamond particle reinforced aluminum alloy flux-cored wire, laser welding and a flux-cored wire technology are combined, and a new way is opened up for application of aluminum alloy and a composite material of the aluminum alloy in a complex environment. According to the method, the strength, the wear resistance and the heat-conducting property of the aluminum alloy welding part can be remarkably improved, and a higher-quality welding solution is provided for the high-end manufacturing fields such as aerospace and automobile manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy welding wire and welding, and in particular relates to a diamond particle reinforced aluminum alloy flux-cored wire and a laser welding method thereof. Background Art

[0002] Aluminum alloy materials are widely used in aerospace, automobile manufacturing, and electronic packaging due to their light weight, high strength, and corrosion resistance. However, due to the high thermal conductivity and high reflectivity of aluminum alloys, defects such as oxidation, pores, and cracks are easily generated during the welding process. These problems seriously affect the quality of the weld and the service life of the welded parts. Therefore, how to effectively improve the welding performance of aluminum alloys, especially the density and strength of the weld, has always been the focus and difficulty in welding process research.

[0003] Laser welding is an ideal choice for aluminum alloy welding due to its advantages such as high energy density, fast welding speed and small heat-affected zone. However, due to the special properties of aluminum alloy (such as high reflectivity and instability of the molten pool), traditional laser welding often faces problems such as insufficient penetration, pores and cracks, which limits its use in complex structural parts, especially in welding special-shaped aluminum alloy plates. Summary of the invention

[0004] One of the purposes of the present invention is to provide a diamond particle reinforced aluminum alloy flux-cored wire, which can not only effectively fill the weld, but also stabilize the molten pool, reduce pores, and improve welding quality. At the same time, Si in the alloy can react with diamond to generate SiC in situ to enhance interface bonding.

[0005] The second object of the present invention is to provide a method for preparing the diamond particle reinforced aluminum alloy cored wire.

[0006] A second object of the present invention is to provide a laser welding method for the diamond particle reinforced aluminum alloy cored wire.

[0007] The invention provides a diamond particle reinforced aluminum alloy cored wire material. The cored wire material comprises 6061 series aluminum alloy powder, metal powder, diamond and graphite powder, wherein the mass fraction of diamond is 1-10wt%, preferably 3-5wt%; the mass fraction of metal powder is 0.1-2wt%, preferably 0.1-1wt%; the mass fraction of graphite powder is 0.1-1wt%, preferably 0.5-1wt%, and the balance is 6061 series aluminum alloy powder.

[0008] Furthermore, the 6061 aluminum alloy powder is a spherical powder with a particle size of 1 to 20 microns, preferably 5 to 8 microns.

[0009] Furthermore, the metal powder is one or more of spherical powders of Cr, V, Ti, and Mo, and the particle size of the powder is 1 to 20 microns, preferably 8 to 10 microns.

[0010] Furthermore, the diamond is single crystal or polycrystalline powder with a particle size of 0.5 to 10 microns, preferably 1 to 5 microns.

[0011] The graphite powder is spherical graphite or flaky graphite, and the powder particle size is 0.5 to 5 microns, preferably 0.5 to 1.2 microns.

[0012] The present invention provides a method for preparing the diamond particle reinforced aluminum alloy cored wire, comprising the following steps:

[0013] S1. Weigh the raw materials according to the above formula, mix them by ball milling, and then use a hollow tube of 6061 aluminum alloy or pure aluminum as a core wire sheath to pack the powder to obtain a core wire;

[0014] S2. Rolling, annealing and drawing the cored wire obtained in step S1 to obtain the diamond particle reinforced aluminum alloy cored wire.

[0015] Furthermore, the ball milling mixing is planetary ball milling, the ball milling speed is 50-100 rpm, the ball milling time is 5-20 hours, the ball-to-material ratio is (10-20):1, argon is used as the protective atmosphere during the ball milling process, and alcohol is used as the ball milling medium. After ball milling, the mixed powder is vacuum dried at 70-120° C. for 1-3 hours to remove residual alcohol.

[0016] Furthermore, in step S1, the powder is filled into a pure aluminum tube or a 6061 aluminum alloy tube with a tube circumference of 5 to 20 mm and a thickness of 0.2 to 1.2 mm, and the powder filling degree is 20% to 40%.

[0017] Preferably, the powder is filled into a pure aluminum tube or a 6061 aluminum alloy tube with a tube circumference of 10 to 15 mm and a thickness of 0.5 to 1 mm, and the powder filling degree is 24% to 36%.

[0018] Furthermore, in step S2, the cored wire obtained in step S1 is rolled several times, the rolling passes are 5 to 10 times, the deformation of a single pass is 15% to 20%, and the final rolling deformation is 80% to 90%; then, in an argon protection environment, annealing treatment is performed at a temperature of 300 to 450° C. for 0.5 to 2 h, and finally, drawing is performed several times, and multiple annealing is performed during the drawing process, the annealing temperature range is 400 to 500° C., and the annealing time is 1 to 3 h, to obtain the diamond particle reinforced aluminum alloy cored wire.

[0019] Furthermore, the diameter of the diamond particle reinforced aluminum alloy core wire is 0.5 to 2 mm.

[0020] The present invention also provides a laser welding method for the diamond particle reinforced aluminum alloy cored wire, comprising the following steps:

[0021] S11. Obtaining a special-shaped aluminum alloy sheet and cleaning it;

[0022] S12. Using laser melting welding, adopting the diamond particle reinforced aluminum alloy flux-cored wire as welding wire, to weld special-shaped aluminum alloy plates.

[0023] Furthermore, in step S11, acetone is used to clean the surface of the aluminum alloy plate to remove oil stains and oxides.

[0024] Furthermore, in step S12, the laser welding machine used is a fiber laser; the laser power used is 1kw~10kw, the welding speed is 10~120mm / s, the welding focus position deviates from the surface by 0~1mm, the feeding speed of the welding wire is 5~100mm / s, and the welding wire incident angle is 10~45°.

[0025] Preferably, the laser power used is 3kw~6kw, the welding speed is 80~120mm / s, the welding focus position deviates from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire is 60~100mm / s, and the welding wire incident angle is 10~45°.

[0026] Furthermore, during the laser welding process, high-purity argon gas or high-purity helium gas with a concentration range of 99.5% to 99.99% is used, and the gas flow rate is 15 to 20 L / min.

[0027] Beneficial effects of the present invention:

[0028] (1) Si in the 6061 aluminum alloy in the aluminum alloy flux-cored wire disclosed in the present invention can react with diamond in situ during welding to generate SiC to enhance interface bonding; diamond itself has the characteristics of high strength, high wear resistance and high thermal conductivity, which can significantly enhance the strength and wear resistance of the weld; the high thermal conductivity of diamond allows heat to be rapidly conducted during welding, avoiding excessive concentration in high-temperature areas and reducing deformation and cracking problems caused by thermal stress; tight interface bonding helps further apply the bearing and thermal conductivity of diamond, reduces the risk of thermal stress and deformation, makes the weld more uniform, and reduces cracking and deformation of welded parts; compared with traditional welding materials, the weld exhibits better mechanical properties and extends the service life of the welded parts;

[0029] (2) The welding method disclosed in the present invention has high energy density and high-speed welding capabilities. Combined with the high thermal conductivity of diamond particles in the flux-cored wire and trace carbide-forming elements, it can ensure that welding can be completed in a short time during the welding process. Carbide particles will be generated during the welding process. These particles can change the fluidity of the molten pool, help stabilize the molten pool, and reduce the formation of pores and cracks during welding; the carbide layer generated by titanium (Ti) and chromium (Cr) can also improve the wettability of the welding molten pool and ensure the uniformity and density of the molten pool. At the same time, these carbide elements can improve the corrosion resistance of the material; in addition, compared with traditional arc welding (such as TIG and MIG), the heat-affected zone (HAZ) of laser welding is smaller, which helps to reduce material damage and improve welding efficiency. Laser welding is suitable for special-shaped aluminum alloy plates and thin-walled structures with complex geometries;

[0030] (3) The weld hardness of the weld welded by the method of the present invention is ≥120HV, the weld strength is ≥310MPa, the thermal conductivity is ≥150W / m·K, and the wear rate is ≤6×10 -6 mm 3 / N·m. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM morphology image of the pure aluminum / diamond cored wire obtained in Example 1;

[0032] Figure 2 This is the SEM morphology of the 6061 aluminum alloy / diamond cored wire obtained in Example 6. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with the embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0035] Example 1

[0036] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 3wt%, the mass fraction of Cr powder was 0.1wt%, the mass fraction of flaky graphite was 0.1wt%, and the balance was 6061 aluminum alloy powder.

[0037] Among them, the particle size of diamond is 8 microns, the particle size of Cr powder is 5 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0038] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0039] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 12 mm and a thickness of 1 mm, with a powder filling degree of 24%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 350°C for 2 hours. Then it was drawn and subjected to multiple intermediate annealings (450°C, 2 hours) to improve the formability, and the final wire diameter was 1.2 mm.

[0040] The obtained welding wire is pure aluminum / diamond cored wire, and the SEM morphology is observed using a scanning electron microscope. Figure 1 shown.

[0041] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 3kw, the welding speed was 100mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 60mm / s, and the welding wire incident angle was 20°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0042] Example 2

[0043] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 5wt%, the mass fraction of Cr powder was 0.5wt%, the mass fraction of flaky graphite was 0.2wt%, and the balance was 6061 aluminum alloy powder.

[0044] Among them, the particle size of diamond is 5 microns, the particle size of Cr powder is 10 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0045] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0046] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 12 mm and a thickness of 1 mm, with a powder filling degree of 30%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 350°C for 2 hours. Then it was drawn and subjected to multiple intermediate annealings (450°C, 2 hours) to improve the formability, and the final wire diameter was 1.2 mm.

[0047] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 3kw, the welding speed was 100mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 60mm / s, and the welding wire incident angle was 20°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0048] Example 3

[0049] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 10wt%, the mass fraction of Ti powder was 0.5wt%, the mass fraction of flaky graphite was 0.2wt%, and the balance was 6061 aluminum alloy powder.

[0050] Among them, the particle size of diamond is 5 microns, the particle size of Ti powder is 10 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0051] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0052] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 12 mm and a thickness of 1 mm, with a powder filling degree of 30%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 450°C for 2 hours. Then it was drawn and subjected to multiple intermediate annealings (450°C, 2 hours) to improve the formability, and the final wire diameter was 1.0 mm.

[0053] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 3kw, the welding speed was 100mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 60mm / s, and the welding wire incident angle was 20°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0054] Example 4

[0055] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 10wt%, the mass fraction of Cr powder was 1wt%, the mass fraction of flaky graphite was 0.2wt%, and the balance was 6061 aluminum alloy powder.

[0056] Among them, the particle size of diamond is 5 microns, the particle size of Cr powder is 5 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0057] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0058] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 12 mm and a thickness of 1 mm, with a powder filling degree of 30%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 350°C for 2 hours. Then it was drawn and subjected to multiple intermediate annealings (450°C, 2 hours) to improve the formability, and the final wire diameter was 1.5 mm.

[0059] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 3kw, the welding speed was 100mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 60mm / s, and the welding wire incident angle was 20°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0060] Example 5

[0061] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 3wt%, the mass fraction of Ti powder was 0.25wt%, the mass fraction of Cr powder was 0.25wt%, the mass fraction of flaky graphite was 0.2wt%, and the balance was 6061 aluminum alloy powder.

[0062] Among them, the particle size of diamond is 2 microns, the particle size of Ti powder and Cr powder is 10 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0063] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0064] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 12 mm and a thickness of 0.8 mm, with a powder filling degree of 30%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 350°C for 2 hours. Then it was drawn and subjected to multiple intermediate annealings (450°C, 2 hours) to improve the formability, and the final wire diameter was 1.8 mm.

[0065] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 5kw, the welding speed was 110mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 80mm / s, and the welding wire incident angle was 45°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0066] Example 6

[0067] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 5wt%, the mass fraction of Cr powder was 0.5wt%, the mass fraction of flaky graphite was 0.2wt%, and the balance was 6061 aluminum alloy powder.

[0068] Among them, the particle size of diamond is 5 microns, the particle size of Cr powder is 5 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0069] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon gas with a purity of 99.5% was used for protection throughout the ball milling process. Alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0070] The obtained mixed powder was filled into a 6061 aluminum alloy hollow tube with a circumference of 12 mm and a thickness of 1 mm, with a powder filling degree of 30%, and then rolled, with 8 rolling passes and a final deformation of 90%. After rolling, it was annealed at 350°C for 2 hours. Then it was drawn, and after multiple intermediate annealings (450°C, 2 hours) to improve the formability, the final wire diameter was 1.0 mm.

[0071] The obtained welding wire is 6061 aluminum alloy / diamond core wire, and the SEM morphology is observed using a scanning electron microscope. Figure 2 shown.

[0072] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 3kw, the welding speed was 100mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 60mm / s, and the welding wire incident angle was 20°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0073] Comparative Example 1

[0074] The raw materials were weighed according to the following formula: the mass fraction of diamond particles was 3wt%, the mass fraction of Cr powder was 0.1wt%, the mass fraction of flaky graphite was 0.1wt%, and the balance was 6061 aluminum alloy powder.

[0075] Among them, the particle size of diamond is 8 microns, the particle size of Cr powder is 5 microns, the particle size of flaky graphite is 5 microns, and the particle size of 6061 aluminum alloy is 10 microns.

[0076] The above raw materials were uniformly mixed and ball-milled using a planetary ball mill for 5 hours at a ball milling speed of 50 rpm and a ball-to-material ratio of 10:1. Argon was used for protection during the entire ball milling process and alcohol was used as the ball milling medium. After ball milling, the mixed powder was placed in a vacuum drying furnace and dried at 90° C. for 2 hours to remove residual alcohol to obtain a mixed powder.

[0077] The obtained mixed powder was filled into a pure aluminum hollow tube with a circumference of 8 mm and a thickness of 1 mm, and then rolled and drawn. After multiple intermediate annealing treatments (450°C, 2 hours) to improve the formability, the final welding wire diameter was 1 mm.

[0078] The obtained welding wire was used to weld aluminum alloy plates by electric welding, using 99.99% pure argon as the shielding gas, with a gas flow rate of 18L / min, a MIG welding current of 220A, and a welding voltage of 25V.

[0079] Comparative Example 2

[0080] The welding wire is 1070 pure aluminum strip with a skin of 10×1mm and a filling rate of 24%. The filling wire is drawn and reduced to a diameter of 1.2mm. The chemical composition of the flux core is 26% metal Zn powder, 12% metal Mg powder, 7.5% metal Cu powder, 0.9% metal Mn powder, 1.0% metal Cr powder, 8% composite micro-nano Mo-TiC particles, and the remainder is pure aluminum powder.

[0081] The obtained welding wire was used to weld the special-shaped aluminum alloy plate by laser melting. Acetone was used to clean the surface of the aluminum alloy plate before welding to remove oil and oxides. The laser power used was 5kw, the welding speed was 110mm / s, the welding focus position deviated from the surface by 0.5mm to ensure the depth and stability of the molten pool, the feeding speed of the welding wire was 80mm / s, and the welding wire incident angle was 45°. High-purity argon was used as the shielding gas during the laser welding process, and the gas flow rate was 20L / min.

[0082] The welds obtained in the above Examples 1 to 5 and Comparative Examples 1 to 2 were tested, and the results are shown in the following table.

[0083] Table 1 Weld seam detection results of the embodiments and comparative examples

[0084] Implementation Methods Weld hardness Weld strength Weld wear rate Weld thermal conductivity Example 1 121.5HV 334.9MPa <![CDATA[5.7×10 -6 mm 3 / N·m]]> 167.3W / m·K Example 2 125.4HV 347.8MPa <![CDATA[5.4×10 -6 mm 3 / N·m]]> 154.2W / m·K Example 3 127.2HV 340.5MPa <![CDATA[5.8×10 -6 mm 3 / N·m]]> 155.2W / m·K Example 4 122.2HV 337.26MPa <![CDATA[5.8×10 -6 mm 3 / N·m]]> 151.3W / m·K Example 5 122.5HV 338.25MPa <![CDATA[5.5×10 -6 mm 3 / N·m]]> 161.9W / m·K Example 6 130.5HV 373.2MPa <![CDATA[4.2×10 -6 mm 3 / N·m]]> 166.2W / m·K Comparative Example 1 91.8HV 302.94MPa <![CDATA[9.2×10 -5 mm 3 / N·m]]> 100.2W / m·K Comparative Example 2 84.7HV 279.51MPa <![CDATA[8.1×10 -4 mm 3 / N·m]]> 96.5W / m·K

[0085] It can be seen from the data in the above table that the weld obtained by the method of the present invention is significantly higher than the comparative example data in weld hardness, weld strength, weld wear rate and weld thermal conductivity.

Claims

1. A diamond particle reinforced aluminum alloy cored wire, characterized in that: The core material includes 6061 series aluminum alloy powder, metal powder, diamond and graphite powder, wherein the mass fraction of diamond is 1-10wt%; the mass fraction of metal powder is 0.1-2wt%; the mass fraction of graphite powder is 0.1-1wt% and the remainder is 6061 series aluminum alloy powder.

2. The diamond particle reinforced aluminum alloy cored wire according to claim 1, characterized in that: The 6061 aluminum alloy powder is spherical powder with a particle size of 1 to 20 microns.

3. The diamond particle reinforced aluminum alloy cored wire according to claim 1, characterized in that: The metal powder is one or more of spherical powders of Cr, V, Ti and Mo, and the particle size of the powder is 1 to 20 microns.

4. The diamond particle reinforced aluminum alloy cored wire according to claim 1, characterized in that: The diamond is single crystal or polycrystalline micro powder with a particle size of 0.5 to 10 microns.

5. The diamond particle reinforced aluminum alloy cored wire according to claim 1, characterized in that: The graphite powder is spherical graphite or flaky graphite, and the powder particle size is 0.5 to 5 microns.

6. A method for preparing the diamond particle reinforced aluminum alloy cored wire according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh the raw materials according to the above formula, mix them by ball milling, and then use a hollow tube of 6061 aluminum alloy or pure aluminum as a core wire sheath to pack the powder to obtain a core wire; S2. Rolling, annealing and drawing the cored wire obtained in step S1 to obtain the diamond particle reinforced aluminum alloy cored wire.

7. The method for preparing the diamond particle reinforced aluminum alloy cored wire according to claim 6, characterized in that: The ball milling mixing is planetary ball milling, the ball milling speed is 50-100 rpm, the ball milling time is 5-20 hours, the ball-to-material ratio is (10-20):1, argon is used as a protective atmosphere during the ball milling process, alcohol is used as a ball milling medium, and after ball milling, the mixed powder is vacuum dried at 70-120° C. for 1-3 hours to remove residual alcohol.

8. The method for preparing the diamond particle reinforced aluminum alloy cored wire according to claim 6, characterized in that: In step S1, the powder is filled into a pure aluminum tube or a 6061 aluminum alloy tube with a tube circumference of 5 to 20 mm and a thickness of 0.2 to 1.2 mm, and the powder filling degree is 20% to 40%; In step S2, the cored wire obtained in step S1 is rolled several times, the rolling passes are 5 to 10 times, the deformation of each pass is 15% to 20%, and the final rolling deformation is 80% to 90%; then, in an argon protection environment, annealing is performed at a temperature of 300 to 450° C. for 0.5 to 2 hours, and finally, drawing is performed several times, and multiple annealing is performed during the drawing process, the annealing temperature range is 400 to 500° C., and the annealing time is 1 to 3 hours, so as to obtain the diamond particle reinforced aluminum alloy cored wire; The diameter of the diamond particle reinforced aluminum alloy core wire is 0.5-2 mm.

9. A laser welding method for the diamond particle reinforced aluminum alloy flux-cored wire material according to any one of claims 1 to 5 or the diamond particle reinforced aluminum alloy flux-cored wire material prepared by the preparation method according to any one of claims 6 to 8, characterized in that: The following steps are involved: S11. Obtaining a special-shaped aluminum alloy sheet and cleaning it; S12. Using laser melting welding, adopting the diamond particle reinforced aluminum alloy flux-cored wire as welding wire, to weld special-shaped aluminum alloy plates.

10. The laser welding method of diamond particle reinforced aluminum alloy cored wire according to claim 9, characterized in that: In step S11, acetone is used to clean the surface of the aluminum alloy plate to remove oil stains and oxides; In step S12, the laser welding machine used is a fiber laser; the laser power used is 1kw-10kw, the welding speed is 10-120mm / s, the welding focus position deviates from the surface by 0-1mm, the feeding speed of the welding wire is 5-100mm / s, and the incident angle of the welding wire is 10-45°; During the laser welding process, high-purity argon or high-purity helium with a purity range of 99.5 to 99.9 is used, and the gas flow rate is 15 to 20 L / min.

Citation Information

Patent Citations

  • Preparation method and application of aluminum-based composite welding wire

    CN110578078A

  • Preparation method of nano-carbide reinforced aluminum matrix composite welding wire

    CN112593110A

  • Wear-resistant reinforced flux-cored wire as well as preparation method and application thereof

    CN116652442A

  • Preparation method of diamond aluminum composite material

    CN118563155A

  • Metal-core welding wire and method for forming the same

    EP2913141A1